Pengaruh Profitabilitas, Likuiditas, Dan Solvabilitas Terhadap Opini Audit Going Concern: (Studi Empiris pada Pada Perusahaan Property dan Real Estate Go Public di BEI Periode 2018-2020) - Evy Yulianti; Muhyarsyah Muhyarsyah (Owner : Riset dan Jurnal Akuntansi, 2022)
The survival of a company can be seen from its good financial condition and operational conditions. According to the 2009 Financial Accounting Standards, the fundamental assumption used when making financial statements for companies that have undergone audits by public accountants is that the company will continue to exist. Profitability shows the company's capacity to make money over a certain period of time. There are three financial ratios that are most often used to see the condition of an enterprise's financial performance, namely the liquidity ratio, solvency ratio and profitability ratio. The purpose of this study is to determine the effect of Profitability, Liquidity, Solvency simultaneously affecting the Audit Opinion going concern on Property and Real Estate companies going Public on the IDX in the 2018-2020 Period. The results showed that Profitability had a significant positive effect on the Audit Opinion of going concern on Property and Real Estate companies going public on the IDX for the 2018-2020 period; Liquidity has a significant positive effect on the Audit Opinion going concern on Property and Real Estate companies going public on the IDX for the 2018-2020 period; Solvency has no effect on the Audit Opinion going concern on Property and Real Estate companies Going Public on the IDX for the 2018-2020 Period; and Profitability, Liquidity, Solvency simultaneously influenced the going concern of the Audit Opinion on Property and Real Estate companies going public on the IDX in the period 2018-2020.